An All‐Solid‐State Z‐Scheme g‐C3N4/Ag/Ag3VO4 Photocatalyst with Enhanced Visible‐Light Photocatalytic Performance. Issue 20 (8th June 2017) - Wu, Jiajia; Shen, Xiaoping; Miao, Xuli; Ji, Zhenyuan; Wang, Jiheng; Wang, Ting; Liu, Miaomiao
Abstract : An all‐solid‐state Z‐scheme g‐C3 N4 /Ag/Ag3 VO4 photocatalyst was synthesized by a facile two‐step reaction route, during which Ag nanoparticles were first deposited on graphitic carbon nitride (g‐C3 N4 ) nanosheets by photochemical reduction of Ag +, and then the remnant Ag + ions reacted with VO4 3– to form Ag3 VO4 nanoparticles on the surface of g‐C3 N4 /Ag. The photocatalytic activity of the as‐synthesized g‐C3 N4 /Ag/Ag3 VO4 photocatalyst for the degradation of rhodamine B was remarkably enhanced relative to that of g‐C3 N4 and Ag3 VO4, as well as that of g‐C3 N4 /Ag and g‐C3 N4 /Ag3 VO4 . The enhanced photocatalytic performance of g‐C3 N4 /Ag/Ag3 VO4 was attributed to the formation of an all‐solid‐state Z‐scheme system, in which the Ag nanoparticles serve as electron‐shuttle mediators in constructing the Z‐scheme and thus prolong the lifetime of electrons and holes photogenerated by g‐C3 N4 and Ag3 VO4, respectively. The excellent photocatalytic performance of g‐C3 N4 /Ag/Ag3 VO4 suggests that this material would be promising for use in the degradation of organic pollutants and provides a new clue for the development of novel Z‐scheme photocatalytic materials. Abstract : An all‐solid‐state Z‐scheme g‐C3 N4 /Ag/Ag3 VO4 photocatalyst is synthesized by a facile two‐step reaction route. This catalyst exhibits enhanced photocatalytic activity for the degradation of rhodamine B.